Food Estate - Jamson H Tampubolon; Delvian Delvian; Abdul Rauf (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2024)
ABSTRACT Food functions as a pillar of national development and plays a role in maintaining a country’s economic, social and political stability of a country, all of which must be fulfilled by the state. Many countries are facing global food problems, leading to significant increases in commodity prices. The Indonesian government launched a National Food Storage Development Strategy to overcome the food crisis. The